Thermal simulation of microelectrode machining process during block electrical discharge grinding - Baocheng Xie; Chenhao Xu; Rongzheng Yao; Jinting Hou; Boxiong Dong; Yuan Zhang (Case Studies in Thermal Engineering, 2024)
Electrical discharge machining is widely used in aerospace industries, semiconductor applications, micro-electromechanical systems, and other fields of the machining of micro-holes, micro-shafts, and micro-structures due to non-contact stress during the electrical discharge machining process. In the electrical discharge machining process, the machining precision of electrical discharge machining depends on the dimensional precision of the tool electrode, therefore, the machining process of microelectrode has attracted growing concern. In this study, a thermal model of the microelectrode machining process was proposed to simulate the formation process of microelectrode based on the temperature distribution during block electrical discharge grinding of the microelectrode process. According to the microelectrode machining process, the thermal model considers the main influential factors such as random distribution of discharge points, time-dependent discharge channel radius, Gauss heat source, phase transformation latent heat, etc. Through the thermal simulation analysis, the temperature distribution and the dynamic spark-erosion process of the microelectrode based on random repetitive spark discharges were obtained during block electrical discharge grinding of the microelectrode. Besides, it is found that the maximum temperature value and discharge crater volume of the electrode surface fluctuate and gradually decrease with the increase of discharge times. In addition, the effect of pulse width on the machining process of microelectrode was investigated by numerical simulation and block electrical discharge grinding of microelectrode experiment. The results indicated that the crater volume and the maximum temperature value on the surface of the microelectrode increased with the increase of pulse width. The formation process of microelectrode was considered a significant indicator to determine the machining precision and machining efficiency of the electrical discharge machining process.